The Mediating Role of Emotional Intelligence in the Causal Relationship Between Spiritual Intelligence and School Attachment and Academic Achievement Among Lower Secondary School Students - Derakhshan, Noushin (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted with the aim of examining the mediating role of emotional intelligence in the causal relationship between spiritual intelligence and school attachment and academic achievement among lower secondary school students. This research is applied in terms of purpose and quantitative, descriptive-survey in terms of method. The participants consisted of 384 lower secondary school students from the city of Tabriz, who were selected using cluster random sampling. The research instruments included the Spiritual Intelligence Questionnaire by Wolman (2011), the Emotional Intelligence Questionnaire by Schering (1998), the Academic Achievement Questionnaire by Pham and Taylor (1994), and the School Attachment Questionnaire by Motton et al. (1993). Data analysis was conducted using structural equation modeling and the Sobel test in SmartPLS version 3.1.1 at a significance level of 0.05. The results indicated that the research model demonstrated a good fit. Spiritual intelligence had a significant effect on school attachment (t = 5.134, p = 0.001), academic achievement (t = 5.289, p = 0.001), and emotional intelligence (t = 25.850, p = 0.001). Emotional intelligence also had a significant effect on school attachment (t = 6.697, p = 0.001) and academic achievement (t = 9.179, p = 0.001). Furthermore, emotional intelligence played a mediating role in the effect of spiritual intelligence on school attachment (z = 8.674, p = 0.001) and academic achievement (z = 9.715, p = 0.001). Therefore, students with higher levels of emotional intelligence and spiritual intelligence exhibit stronger attachment to school and achieve higher levels of academic performance.